2006
DOI: 10.1088/0953-8984/18/29/009
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism and origin of non-monotonous concentration dependence of the bulk modulus in Fe-rich alloys with Si, Ge and Sn: a first-principles study

Abstract: Using the first-principles calculations based on the coherent potential approximation, we study the electronic structure, magnetic moments and the bulk modulus of FeX alloys with IVB group elements (X = Si, Ge, Sn) in the Fe-rich concentration range (x = 0.0-0.25), which form a stability region of bcc-related phases. In agreement with experiment, our calculations reproduce well a peculiar non-monotonous behaviour of the bulk modulus in Fe-Si alloys with increasing Si concentration. Such a dependence is found f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
5
22
0
1
Order By: Relevance
“…This was attributed to the increasing number of p-p and p-d bonds with the addition of Ge and Sn in Fe. [100] Taking L1 2 -Ni 3 Sn as a prototypical case, in Section B, we show that the bonding mechanism is dominated by p-d hybridization.…”
Section: A Phase Stability Of Ni-sn Intermetallicsmentioning
confidence: 94%
See 1 more Smart Citation
“…This was attributed to the increasing number of p-p and p-d bonds with the addition of Ge and Sn in Fe. [100] Taking L1 2 -Ni 3 Sn as a prototypical case, in Section B, we show that the bonding mechanism is dominated by p-d hybridization.…”
Section: A Phase Stability Of Ni-sn Intermetallicsmentioning
confidence: 94%
“…[79] Our observations of an increase in the equilibrium atomic volume and a concomitant decrease in the bulk modulus are consistent with the earlier first-principles results of bcc Fe 1-x Ge x and Fe 1-x Sn x alloys, using coherent potential approximation. [100] Both Ge and Sn increase the atomic volume of the bcc solid solution of Fe; they also decrease the bulk modulus. This was attributed to the increasing number of p-p and p-d bonds with the addition of Ge and Sn in Fe.…”
Section: A Phase Stability Of Ni-sn Intermetallicsmentioning
confidence: 99%
“…Therefore, based on the data on only the concentration induced expan sion, one cannot obtain information on the local ε loc 1 ( ) deformations. The calculated deviation from Vegard's law can be attributed to the transformation of the elec tronic structure with increasing alloying element con centration, which plays a significant role in the prop erties of these alloys [25].…”
Section: Discussionmentioning
confidence: 93%
“…Such a magnetic-moment-induced volume change is known as the magneto-volume effect. 21 Taking B as an example of the seven elastic properties under consideration, we evaluated the change in B induced by magnetic moments using Stoner's model of itinerant magnetism 22 and revealed that this model explains well the Si concentration dependence of B up to 9.4 at.%Si, but it cannot interpret the drastic change in B as the Si concentration increases above 9.4 at.%Si. 1 In the range of higher Si concentrations from 10.9 to 12.5 at.%Si, there should be another reason behind the recovery of the elastic properties as displayed in Fig.…”
Section: Elastic Propertiesmentioning
confidence: 99%